Fast and low loss flexoelectro-optic liquid crystal phase modulator with a chiral nematic reflector - Wang, X; Fells, J; Elston, S; Yip, C; Ali, T; Lin, J; Welch, C; Mehl, G; Booth, M; Wilkinson, T; Morris, S (University of Oxford, 2019)
Most data is measured during the experiment and Matlab code is used to simulate the system